2009
DOI: 10.1089/cpb.2009.0006
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Young Adults Develop a Passion for Internet Activities? The Associations among Personality, Revealing “True Self” on the Internet, and Passion for the Internet

Abstract: This study examines the associations of harmonious passion (HP) and obsessive passion (OP) for Internet activities with Eysenckian personality dimensions in a sample of 421 university students. Results show that psychoticism correlates positively with both HP and OP; extroversion correlates positively with HP only; and neuroticism has no correlation with passion for Internet activities. Additionally, the study examines participants' tendency to express their "true self" on the Internet, and the results reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 15 publications
0
46
0
4
Order By: Relevance
“…Higher frequency of Internet use, lack of perseverance (an aspect of impulsivity), and online group membership significantly predicted problematic Internet use in Australian students (50). The personality dimension of psychoticism correlated positively with the constructs of harmonious and obsessive passion, and this was mediated by the tendency to express one's true self on the Internet in Turkish adolescents (51). South Korean Internet-addicted adolescents had more interpersonal problems than healthy users (30).…”
Section: Factors Predictive Of Problematic Internet Usementioning
confidence: 92%
“…Higher frequency of Internet use, lack of perseverance (an aspect of impulsivity), and online group membership significantly predicted problematic Internet use in Australian students (50). The personality dimension of psychoticism correlated positively with the constructs of harmonious and obsessive passion, and this was mediated by the tendency to express one's true self on the Internet in Turkish adolescents (51). South Korean Internet-addicted adolescents had more interpersonal problems than healthy users (30).…”
Section: Factors Predictive Of Problematic Internet Usementioning
confidence: 92%
“…Only a handful of studies have looked at the role personality as a predictor of passion. Such research reveals that general dispositions like the Big Five only weakly predict the two types of passion (Balon, Lecoq, & Rimé, 2013;Tosun & Lajunen, 2009). However, other studies have shown that more specific dispositions such as self-oriented perfectionism predicts harmonious passion while socially prescribed perfectionism predicts obsessive passion (VernerFilion & Vallerand, 2015).…”
Section: Impulsivity (Upps) As a Predictor Of Passionmentioning
confidence: 96%
“…Personality factors such as lack of perseverance (Mottram & Fleming, 2009), psychoticism (Tosun & Lajunen, 2009), and neuroticism, sensation seeking, and aggressiveness (Mehroof & Griffiths, 2010) have been found to be associated with Internet addiction. Sensation seeking among Chinese Internet users was reported by Shi, Chen, and Tian (2011).…”
Section: Personality and Psychosocial Factors Associated With Iadmentioning
confidence: 99%